Studi Umur Simpan Selai Buah Pedada (Sonneratia caseolaris) Berdasarkan Tempat Penyimpanan - Indri Setianingsih (Universitas Pendidikan Ganesha, 2024)
Indonesia has a unique ecosystem and has an important role in coastal areas which are often called mangrove forests. One of them is in Surabaya, precisely in Wonorejo which is also a place of education and there are mangrove tours in it. Mangroves can be used in economic terms to be used as various types of processed food, drinks, one of which is jam. Mangrove forests in it there are many plants, one of which is the species Sonneratiaceae (Sonneratia). High nutrition in the content of pedada fruit is used and processed to be used as several food products, one of which is jam. From this study aims to provide information for readers how long the study of the shelf life of pedada fruit if used as jam.